PENGARUH EKSTRAK KOPI ROBUSTA TERHADAP EKSPRESI OSTEOKALSIN PADA OSTEOBLAS SELAMA PERGERAKAN GIGI ORTODONTI - Herniyati Herniyati (Jurnal Teknosains, 2016)
The objective of  research is  to determine the expression of osteocalcin on osteoblasts during orthodontic tooth movement after administration robusta coffee extract. Materials and Methods: 16 rats  were divided into 2 groups: group K: rats applied with orthodontic mechanical force (OMF) and  group P: OMF +  coffee robusta extract of 20mg /100 g of BW. OMF was conducted by applying  ligature wire on permanent maxillary right first molar and both permanent maxillary incisivus. Subsequently, the permanent maxillary right first molar  moved to mesial with Ni-Ti orthodontic closed coil spring. Observations were made on day 15 by immunohistochemical examination to determine the expression of osteocalcin. Results: Robusta coffee extract  improved the expression of osteocalcin in the compression and tension areas (p <0.05). Expression of osteocalcin in  tension area  larger than that in compression area (p <0.05). Conclusion: The administration of Robusta coffee extract  increases the expression of osteocalcin, which can increase alveolar bone remodeling.